The Legend of the Candy Cane - Walburg, Lori.; Bernardin, James (Grand Rapids, Mich. : Zondervan Pub., 1997)
With the help of a little girl, a mysterious stranger tells the story of the candy cane to the people of a small prairie town during Christmas time at the turn of the century.
Keywords: Jesus Christ -- Nativity; Candy canes -- Fiction; Christmas -- Fiction